Pengaruh Sosialisasi Pajak, Pengetahuan Pajak, Pemahaman Pajak, dan Kesadaran Pajak terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan di Kelurahan Naikliu Kecamatan Amfoang Utara Kabupaten Kupang - Venci Ilona Lake; Petrus E. de Rosari; Novi Theresia Kiak (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of tax socialization, tax knowledge, tax understanding, and tax awareness on land and building tax compliance. This research was carried out in Naikliu Village, Nort Amfoang Utara District with a population of 534 taxpayers. The method used in selecting the sample was random sampling using the slovin formula and was determined as many as 100 respondents. This type of research is included in quantitative descriptive with survey methods. The type of data used in this research is primary data obtained by distributing 100 questonnaires and the total number of questionnaires that can be processed is 100. The statistical method used multiple linear regression analysis with the help of SPSS 25 application software. The results of this research show that the Socialization variabel tax, tax knowledge, tax understanding, are partially insignificant to taxpayer compliance, meanwhile taxpayer awareness partyally has a significant effect on land and building tax compliance. Meanwhile, the variables of tax socialization, tax knowledge, tax understanding, and tax awareness together simultaneosly influence taxpayer compliance.